1997
DOI: 10.1212/wnl.49.4.960
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe epilepsy in childhood: Clinical, EEG, and neuroimaging findings and syndrome classification in a cohort with new-onset seizures

Abstract: Sixty-three children with new-onset temporal lobe epilepsy (TLE) underwent extensive clinical, EEG, and neuroimaging investigation as part of a prospective, community-based cohort study of the natural history of TLE in childhood. Complex partial seizures occurred in 94% of the children, and tonic-clonic seizures occurred in 14%. Developmental, behavioral, or learning problems were present in 38%. Eighteen children (29%) had a significant illness/event prior to the onset of TLE, including febrile status epilept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
2
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 25 publications
3
75
2
5
Order By: Relevance
“…No association was obtained between MTS side and cognitive defi ciency, delay in speaking or age focal seizure onset. The results in children submitted to surgery are equal to those found in adults 4 . Comparing the group of operated with that of non-operated patients of the present study, there was no statistically signifi cant difference regarding seizure control, but there was difference as concerns the used AED number, since the non-operated children used a higher number of AED, a fact directly related to control of seizures and consequently to the patients' quality of life.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…No association was obtained between MTS side and cognitive defi ciency, delay in speaking or age focal seizure onset. The results in children submitted to surgery are equal to those found in adults 4 . Comparing the group of operated with that of non-operated patients of the present study, there was no statistically signifi cant difference regarding seizure control, but there was difference as concerns the used AED number, since the non-operated children used a higher number of AED, a fact directly related to control of seizures and consequently to the patients' quality of life.…”
Section: Discussionmentioning
confidence: 58%
“…In children with temporal lobe epilepsy, MTS is considered an infrequent etiology 4,5 , but with the advances in neuroimaging, MTS which was thought to be a disease of adults, started to be diagnosed at an increasingly younger age [6][7][8][9] .…”
mentioning
confidence: 99%
“…In both children and adults, hippocampal sclerosis is less frequently detected by MRI at the onset of temporal lobe epilepsy as compared to chronic refractory temporal lobe epilepsy [3][4][5] . The low prevalence of hippocampal sclerosis in early childhood suggests that MRI-detectable hippocampal sclerosis might be part of a multistage or progressive changes 6) .…”
Section: Discussionmentioning
confidence: 99%
“…The authors have concluded recently that this syndrome was an atypical presentation of benign epilepsy with centro-temporal paroxysms (5) . Harvey et al (6) studying clinical, electroencephalographic (EEG) and neuroimaging features of 63 children with recently diagnosed TLE, classified it in three subgroups, according to the etiology: TLE with developmental malformations (cortical dysgenesis, arachnoid cyst or low grade tumor), TLE with mesial temporal sclerosis (MTS) and significant antecedents (complex febrile seizure, traumatic brain injury or meningoencephalitis), and cryptogenic TLE. This latter group had a better seizure and psychological prognosis and may represent a benign syndrome of TLE.…”
Section: Historical Datamentioning
confidence: 99%
“…They are characterized clinically by refractory complex partial seizures (CPS) with onset in childhood (16) . Pleomorphic xanthoastrocytoma is rare and affects adolescents and young adults (6) . Oligodendrogliomas are infiltrative tumors, which affect children with an incidence of 7-14% (8,9) .…”
Section: Etiologymentioning
confidence: 99%